Suicide amongst the Inuit of Nunavut: An Exploration of Life Trajectories - William Affleck; Eduardo Chachamovich; Nadia Chawky; Guy Beauchamp; Gustavo Turecki; Monique Séguin (International Journal of Environmental Research and Public Health, 2020)
This article reports results of the life trajectories from 92 Inuit who died by suicide, matched for age and gender with 92 living-controls. A proxy-based procedure and semi-structured interviews with informants were conducted to obtain trajectories of developmental events occurring over the life course for suicide and community-matched controls. Results from this research indicate two different trajectories that differentiate the control-group from the suicide-group throughout the life course. Even though the number of suicide attempts are similar between both groups, the suicide-group had a more important burden of adversity, which seemed to create a cascading effect, leading to suicide.